Pembelajaran Model Think Pair Square untuk Meningkatkan Motivasi dan Hasil Belajar Peserta Didik - Ambar Suryaningsih (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
This study aims to increase learning motivation and learning outcomes of students using a think pair square type cooperative learning model. This study is a class action research conducted in two cycles. The results showed that in the first cycle learning results were obtained with an average of 60, while the average percentage of learning motivation of 61.01% increased quite significantly in the second cycle with the acquisition of an average learning outcome value of 75 and the percentage of student learning motivation of 75.04%. It can be concluded that learning carried out with the think pair square type cooperative learning model can increase learning motivation and student learning outcomes.